Under the magnolias [large type] - Lowe, T. I. (Tonya) (Thorndike Press large print Christian fiction series., 2023)
"Magnolia, South Carolina, 1980 Austin Foster is barely a teenager when her mama dies giving birth to twins, leaving her to pick up the pieces while holding her six siblings together and doing her best to stop her daddy from retreating into his personal darkness.Scratching out a living on the family's tobacco farm is as tough as it gets. When a few random acts of kindness help to ease the Fosters' hardships, Austin finds herself relying upon some of Magnolia's most colorful citizens for friendship and more. But it's next to impossible to hide the truth about the goings-on at Nolia Farms, and Austin's desperate attempts to save face all but break her.Just when it seems she might have something more waiting for her--with the son of a wealthy local family who she's crushed on for years--her father makes a choice that will crack wide-open the family's secrets and lead to a public reckoning. There are consequences for loving a boy like Vance Cumberland, but there is also freedom in the truth."--